Phosphorus and aluminium mobilisation in ferralsols: effects of local sediment amendments, liming and straw application in a lab study - Scherwietes, Eric; Stein, Mathias; Six, Johan; Bawen, Titus Kiplagat; Schaller, Jörg (Frontiers in Environmental Science, 2025)
Phosphorus (P) activation is a major challenge for agriculture on tropical soils like Ferralsols in East Africa, mainly due to soil acidity and high mobility of aluminium (Al). Strategies such as local sediment amendments and liming have shown potential to improve P availability in these soils. In this study, we performed three incubation experiments of soil slurries under laboratory conditions to investigate the temporal mobilisation of silicon (Si), iron (Fe), Al, and P by local sediment amendments. The three incubation experiments consisted of soil slurries with the following treatments: (i) solely two local sediment amendments (from Baringo and Nakuru) over 28 days; (ii) additional 0.15% liming treatment over 61 days; and (iii) straw addition under anoxic conditions over 80 days. We found that Fe reduction by straw addition increased P concentration in the soil solution by a factor of ten, independent of the sediment material. However, the effects of liming and sediment additions on P mobilisation were short-termed, characterised by an initial rapid release of P followed by a quick re-adsorption, precipitation or uptake of available P by soil microbes. Nevertheless, liming and sediment additions could have an indirect effect on P availability, as reduced Al reactivity—resulting from Si addition and potential Al-Si binding, as well as from the increase in pH—can lead to decreased P fixation.